Antimicrobial Resistance in Escherichia coli and Staphylococcus aureus After the COVID-19 Pandemic - Edgardo Joseph Bacabac; Rubenito Gomez; Pompe Cruz Festin; Florencio Abesamis; Andrew Huttley (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
Antimicrobial resistance (AMR) has emerged as one of the most pressing post-pandemic health threats, particularly in low- and middle-income countries such as the Philippines. During the COVID-19 pandemic, widespread empirical use of antibiotics accelerated selective pressure on bacterial pathogens, potentially intensifying resistance trends. This study aims to analyze changes in the resistance patterns of Escherichia coli and Staphylococcus aureus to first-line antibiotics before (2018–2019) and after (2022–2023) the pandemic, and to evaluate the implementation of Antibiotic Stewardship Programs (ASP) in government hospitals. A retrospective observational design was applied using WHONET microbiological data from three public hospitals across Luzon, Visayas, and Mindanao, combined with semi-structured interviews involving infectious disease physicians and clinical pharmacists. Statistical and thematic analyses revealed a significant increase in resistance: E. coli resistance to ciprofloxacin rose from 32% to 48%, and MRSA prevalence increased from 15% to 27%. Hospitals with active ASPs reported smaller resistance increases (Δ = +8%) compared to those without consistent stewardship activities (Δ = +18%). These findings highlight the critical role of structured ASPs, robust microbiology infrastructure, and real-time data integration in mitigating AMR escalation. Strengthening ASP implementation, expanding diagnostic capacity, and integrating surveillance systems into national health information frameworks are essential policy priorities. Future research should explore genomic approaches and digital ASP models to enhance precision in antibiotic governance and resistance control in the post-pandemic era.